2016
DOI: 10.5194/acp-16-11807-2016
|View full text |Cite
|
Sign up to set email alerts
|

Can simple models predict large-scale surface ocean isoprene concentrations?

Abstract: Abstract. We use isoprene and related field measurements from three different ocean data sets together with remotely sensed satellite data to model global marine isoprene emissions. We show that using monthly mean satellite-derived chl a concentrations to parameterize isoprene with a constant chl a normalized isoprene production rate underpredicts the measured oceanic isoprene concentration by a mean factor of 19 ± 12. Improving the model by using phytoplankton functional type dependent production values and b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
121
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(134 citation statements)
references
References 59 publications
(99 reference statements)
13
121
0
Order By: Relevance
“…We neglected the loss rates of isoprene due to biological degradation and physical mixing because they are low compared to k CHEM and k AS (Palmer and Shaw, 2005;Booge et al, 2016), meaning that the resulting P need value can be seen as a minimum needed production rate.…”
Section: Indirect Calculation Of Isoprene Production Ratesmentioning
confidence: 99%
See 3 more Smart Citations
“…We neglected the loss rates of isoprene due to biological degradation and physical mixing because they are low compared to k CHEM and k AS (Palmer and Shaw, 2005;Booge et al, 2016), meaning that the resulting P need value can be seen as a minimum needed production rate.…”
Section: Indirect Calculation Of Isoprene Production Ratesmentioning
confidence: 99%
“…Isoprene production rates of different PFTs were determined in laboratory phytoplankton culture experiments (see a collection of literature values: Table 2 in Booge et al, 2016) and were used here to calculate isoprene production from measured PFTs in the field. These literature studies showed that isoprene production rates are light dependent, with increasing production rates at higher light levels (Shaw et al, 2003;Gantt et al, 2009;Bonsang et al, 2010;Meskhidze et al, 2015).…”
Section: Direct Calculation Of Isoprene Production Ratesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, satellite PG data were used to assess globally particulate organic carbon export (Mouw et al, 2016), for detection of regional HAB events (e.g., Kurekin et al, 2014), the estimation of recruitment of juvenile fish (Trzcinski et al, 2013) and for inferring globally oceanic emissions of volatile organic compounds (Arnold et al, 2009;Booge et al, 2016).…”
Section: Approachmentioning
confidence: 99%